EMPOWERING FUTURES: Unveiling Zakat's Vital Role Economic Development and Legal Framework in Malaysia's - Daud, Mohd Zaidi; Mohd Noh, Mohd Shahid; Fidhayanti, Dwi; Mat Hussin, Mohd Norhusairi (Jurisdictie: Jurnal Hukum dan Syariah, 2025)
This study investigates the vital role of zakat in Malaysia's economic development within the context of its legal and public policy frameworks. Zakat, an obligatory form of almsgiving in Islam, serves as a critical instrument for wealth redistribution and social welfare. The background of this study highlights zakat's potential to alleviate poverty, promote social justice, and drive economic empowerment in Muslim-majority countries. The primary objective is to examine how Malaysia's legal provisions, regulatory mechanisms, and public policy initiatives enhance the effectiveness of zakat in achieving these socio-economic goals. The methodology involves a comprehensive review of statutory instruments, state enactments, and administrative practices governing zakat, supported by case study analysis and statistical data on its economic impact. This mixed-methods approach enables a nuanced understanding of the intersection between zakat governance, legal structures, and economic outcomes. The study’s findings reveal that Malaysia's structured legal framework and progressive public policies have significantly improved zakat management, leading to effective poverty alleviation, economic empowerment, community development, and crisis response. Importantly, this research contributes to the fields of law and public policy by illustrating how legal reforms, institutional strengthening, and policy integration can maximize the socio-economic benefits of religious fiscal instruments like zakat, thereby fostering a more equitable and resilient national economy.Penelitian ini mengkaji peranan penting zakat dalam pembangunan ekonomi Malaysia dalam konteks kerangka hukum dan kebijakan publik. Zakat, sebagai kewajiban dalam Islam, berfungsi sebagai instrumen utama dalam redistribusi kekayaan dan kesejahteraan sosial. Latar belakang penelitian ini menyoroti potensi zakat dalam mengentaskan kemiskinan, mempromosikan keadilan sosial, dan mendorong pemberdayaan ekonomi di negara-negara dengan mayoritas Muslim. Tujuan utama penelitian ini adalah untuk menganalisis bagaimana ketentuan hukum, mekanisme regulasi, dan inisiatif kebijakan publik di Malaysia memperkuat efektivitas zakat dalam mencapai tujuan sosial ekonomi tersebut. Metodologi yang digunakan melibatkan tinjauan komprehensif terhadap instrumen hukum, enakmen negara bagian, serta praktik administratif yang mengatur zakat, yang didukung oleh analisis studi kasus dan data statistik terkait dampak ekonomi zakat. Pendekatan metode campuran ini memungkinkan pemahaman yang mendalam mengenai keterkaitan antara tata kelola zakat, struktur hukum, dan hasil-hasil ekonomi. Hasil penelitian menunjukkan bahwa kerangka hukum yang terstruktur dan kebijakan publik yang progresif di Malaysia secara signifikan meningkatkan pengelolaan zakat, sehingga efektif dalam pengentasan kemiskinan, pemberdayaan ekonomi, pembangunan komunitas, serta penanganan krisis. Secara khusus, penelitian ini memberikan kontribusi pada bidang hukum dan kebijakan publik dengan menunjukkan bagaimana reformasi hukum, penguatan kelembagaan, dan integrasi kebijakan dapat memaksimalkan manfaat sosial ekonomi dari instrumen fiskal keagamaan seperti zakat, guna mewujudkan perekonomian nasional yang lebih adil dan tangguh.